Effect of Slag and Recycled Materials on the Performance of Hot Mix Asphalt (AC-BC) - Rindu Twidi Bethary; Bambang Sugeng Subagio; Harmein Rahman; Nyoman Suaryana (Jurnal Teknik Sipil, 2019)
The limitations of road construction materials require alternative materials such as asphalt recycling and utilization of waste potential such as steel slag for aggregate substitutes. In this study, there were tests for slag characteristics and reclaimed asphalt pavement (RAP) then continued with a marshall test to determine the optimum asphalt content (OAC). The nine mixtures planned in this study consist of 10-30% Slag combined with 10-30% RAP with Reclamite as a rejuvenating material. Using a combination of RAP, there is a decrease in the mixing and compaction temperature of 20°C compared to the conventional hot mix. Test results on hot mix asphalt using a combination of RAP and slag generate an increase of 10-30% each using a combined gradation and volume correction. Test result in heat asphalt mixture by using RAP and slag combination with additional of 10-30% each using correction of volume and combined gradation. For the hot mix asphalt with RAP10 and SLAG 10-30 (HMAR10S10-30), the OAC value is 5.83%, 5.95%, and 5.38%, and for the hot mix asphalt with RAP20 and SLAG 10-30 (HMAR20S10- 30), the OAC value obtained is 5.90%, 5.60%, and 5.95%, and for the hot mix asphalt with RAP30 and SLAG 10-30 (HMAR30S10-30), the OAC value is 5.55%, 5.60 %, and 5.33%. Keterbatasan material konstruksi jalan membutuhkan adanya material alternatif seperti daur ulang aspal dan pemanfaatan potensi limbah seperti slag baja untuk pengganti agregat, pada penelitian ini terdapat pengujian karakteristik slag dan daur ulang aspal (RAP) kemudian dilanjutkan dengan pengujian marshall untuk menentukkan kadar aspal optimum (KAO). Sembilan campuran direncanakan dalam penelitian ini yang terdiri dari 10-30% Slag dikombinasikan dengan 10-30% RAP dengan bahan peremaja Reclamite. Dengan menggunakan kombinasi RAP terjadi penurunan temperatur pencampuran dan pemadatan lebih rendah 20°C dibandingkan campuran panas konvensional. Hasil pengujian pada campuran beraspal panas dengan menggunakan kombinasi RAP dan slag dengan penambahan masing-masing sebesar 10-30% menggunakan koreksi volume dan gradasi gabungan, untuk campuran beraspal panas dengan RAP10 dan SLAG 10-30 (HMAR10S10-30) didapatkan nilai KAO sebesar 5,83%, 5,95%, dan 5,38%, sedangkan campuran beraspal panas dengan RAP20 dan SLAG 10-30 (HMAR20S10-30) didapatkan nilai KAO sebesar 5,90%, 5,60%, dan 5,95% dan untuk campuran beraspal panas dengan RAP30 dan SLAG 10-30 (HMAR30S10-30) didapatkan nilai KAO sebesar 5,55%, 5,60%, dan 5,33%.